Mecanismele de construcție și deconstrucție a stigmatizării, în cazul romilor din România - Surdu, Laura (Calitatea Vieții, 2010)
The phenomenon of social prestige is corresponding, at a first glance, only to a social positive identity of an individual. However, prestige also has a negative element and it could be used like bad or negative reputation. The individual who has a negative reputation is probably to be stigmatized. I identified the Roma population from Romania as being stigmatized because of both historical as well as social circumstances. The ways of construction and de-construction of stigma in the case of Roma are personal and social, too. Stygma consciousness is always perceived with various levels of intensity.